Julieta [videorecording (DVD)] - Almodóvar, Pedro; Munro, Alice, 1931-; Suárez, Emma, 1964-; Ugarte, Adriana, 1985-; Grao, Daniel, 1976- (Sony Pictures Home Entertainment, 2017)
Julieta lives in Madrid with her daughter Antia. They both suffer in silence over the loss of Xoan, Antia's father and Julieta's husband. At times, grief doesn't bring people closer, it drives them apart.